2017
DOI: 10.1074/jbc.m117.796920
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the sarco/endoplasmic reticulum (ER) Ca2+-ATPase by thapsigargin analogs induces cell death via ER Ca2+ depletion and the unfolded protein response

Abstract: Calcium (Ca) is a fundamental regulator of cell signaling and function. Thapsigargin (Tg) blocks the sarco/endoplasmic reticulum (ER) Ca-ATPase (SERCA), disrupts Ca homeostasis, and causes cell death. However, the exact mechanisms whereby SERCA inhibition induces cell death are incompletely understood. Here, we report that low (0.1 μm) concentrations of Tg and Tg analogs with various long-chain substitutions at the O-8 position extensively inhibit SERCA1a-mediated Ca transport. We also found that, in both pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
141
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(172 citation statements)
references
References 44 publications
7
141
0
1
Order By: Relevance
“…This dynamic would generate a feed forward loop in which aberrant viral RNA by-products of replication lead to shutdown of translation, and the subsequent generation of more aberrant viral RNA ultimately resulting in viral clearance or the induction of cell death. To formally investigate how the antiviral pathways that target translation would impact IAV biology, we infected cells treated with increasing amounts of thapsigargin, a compound that induces the unfolded protein response (UPR) by inhibiting the function of calcium-dependent chaperones ( Figure 5E) (Sehgal et al, 2017). Consistent with our previous results, these data demonstrated that engagement of the UPR rapidly resulted in loss of NP and a corresponding induction of the host response (as measured by IFN and IFIT1).…”
Section: Defining the Priorities Of Ns1 Antagonism On The Host Responsupporting
confidence: 83%
“…This dynamic would generate a feed forward loop in which aberrant viral RNA by-products of replication lead to shutdown of translation, and the subsequent generation of more aberrant viral RNA ultimately resulting in viral clearance or the induction of cell death. To formally investigate how the antiviral pathways that target translation would impact IAV biology, we infected cells treated with increasing amounts of thapsigargin, a compound that induces the unfolded protein response (UPR) by inhibiting the function of calcium-dependent chaperones ( Figure 5E) (Sehgal et al, 2017). Consistent with our previous results, these data demonstrated that engagement of the UPR rapidly resulted in loss of NP and a corresponding induction of the host response (as measured by IFN and IFIT1).…”
Section: Defining the Priorities Of Ns1 Antagonism On The Host Responsupporting
confidence: 83%
“…FUNDC1 ablation also decreases the levels of the MAM maintenance protein PACS2 . Inhibition of ER Ca 2+ uptake by SERCA initiates UPR and eventually provokes apoptosis . PDK4 inhibition decreases Ca 2+ flux in C2C12 myoblasts .…”
Section: Contacts Between Mitochondria and Other Organellesmentioning
confidence: 98%
“…In addition to the harmful effects of the intracellular release of calcium from the ER, the depletion of calcium itself from this organelle is detrimental (Sehgal et al., ). Sehgal et al.…”
Section: Intracellular Calcium Storesmentioning
confidence: 99%
“…Sehgal et al. () reported that calcium depletion from the ER caused the activation of a cellular pathway called the unfolded protein response (UPR). Among the many physiological functions of the ER, proper protein folding is one function that is impaired in this circumstance (Lin et al., ).…”
Section: Intracellular Calcium Storesmentioning
confidence: 99%
See 1 more Smart Citation